UPAYA PENGEMBANGAN PEMASARAN PRODUK TABUNGAN iB MASLAHAH BANK BJB SYARIAH KCP LIPPO CIKARANG PADA MASA PANDEMI - Vivih Shapira; Heru Mulyanto (DPPM Universitas Pelita Bangsa, 2022)
This study aims to determine the development of marketing strategies for the iB Maslahah savings product at Bank BJB Syariah during the pandemic and the development of socialization to the public about the iB Maslahah savings product at Bank BJB Syariah during the pandemic. The type of data in this study used a qualitative method with a descriptive approach. From the research results, the development of marketing strategies for iB Maslahah savings products is using social media including Twitter, Instagram, Youtube, Facebook, Whatsapp, and Tiktok. In addition, it also uses a desk call and mobile development maslahah. While the development of the socialization of the iB Maslahah savings product that the BJB Syariah bank did, namely through social media, among others, socialization using Instagram and YouTube live streaming.